Comunidades armadas en el Oriente Antioqueño: el caso del E.L.N. en la década del noventa. Colombia (2019)
The present work offers a critical perspective to the emergence of the National Liberation Army (ELN) guerrillas in the Antioquia East in the 1990s. The logic of the paramilitary actor against the organized communities of the East Antioquia in the 1980s serves as a framework to expose the passage of the social struggle to political and armed resistance, and thus, the origin of the ELN in this region of Antioquia. For this, he exposes, in the light of Political Science, the network of power relations: in the social structure (community and civic), in the implementation of paramilitary terror and in the appearance of a guerrilla of a societal type. It is analysed based on the structuralist-Marxist approach, which recognizes a relational and strategic horizon of political-social action that includes the identification of actors, events, scenarios, correlation of forces and structure-conjuncture relationship, based on the literature review of experts and researchers and, semi-structured interview to one (1) life testimonials. It concludes with a series of recommendations for the effective participation of victims in peace building.